FAKTORFAKTOR YANG BERHUBUNGAN DENGAN RISIKO TINGGI OBSTRUCTIVE SLEEP APNEA PADA PASIEN FIBRILASI ATRIUM - Nushrotul Lailiyya,* Sobaryati,* Novia Aiko,* Chaerul Achmad** (NEURONA, 2018)
INTRODUCTION ATRIAL FIBRILLATION AF IS THE MOST FREQUENT CARDIAC ARRHYTHMIA IN THE WORLD AND ASSOCIATED WITH HIGH MORBIDITY AND MORTALITY OBSTRUCTIVE SLEEP APNEA OSA IS STRONGLY ASSOCIATED WITH AF AND ITS PREVALENCE IS 3262 OBSTRUCTIVE SLEEP APNEA SCREENING AND ITS REDUCTION ARE ONE APPROACH TO REDUCE THE RISK OF AND INCREASING THE TREATMENT EFFECTIVENESS OF AF